2021
DOI: 10.3390/vetsci8090171
|View full text |Cite
|
Sign up to set email alerts
|

Survey on the Presence of Bacterial and Parasitic Zoonotic Agents in the Feces of Wild Birds

Abstract: Wild avifauna may act as fecal source of bacterial and parasitic pathogens for other birds and mammals. Most of these pathogens have a relevant impact on human and livestock health which may cause severe disease and economic loss. In the present study, the fecal samples collected from 121 wild birds belonging to 15 species of the genera Anas, Tadorna, Fulica, Arddea, Larus, Falco, Athene, Accipiter, and Columba were submitted to bacteriological and molecular analyses to detect Brucella spp., Coxiella burnetii,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 65 publications
2
7
0
Order By: Relevance
“…The results obtained in the current survey confirm that wild birds can act as reservoirs and spreaders of various pathogens, including antimicrobial-resistant bacteria, as reported by other authors [19][20][21][22].…”
Section: Discussionsupporting
confidence: 91%
“…The results obtained in the current survey confirm that wild birds can act as reservoirs and spreaders of various pathogens, including antimicrobial-resistant bacteria, as reported by other authors [19][20][21][22].…”
Section: Discussionsupporting
confidence: 91%
“…Most of the animals whose feces were positive were birds usually living in humid environments. These results are in agreement with those of other studies in which water fowl, in particular Anas crecca and Anas penelope , were found to be infected by C. burnetii [ 5 , 23 ]. The detection of the pathogen in feces of different avian species [ 24 ] is relevant, because it shows that infected birds can excrete and disseminate the bacteria in the environment.…”
Section: Coxiella Burnetiisupporting
confidence: 93%
“…Passeriformes and pigeons, but also gulls and waterfowl, are often present in farm areas and can act as a source of infections for livestock, causing relevant economic losses. The role of birds as vectors of bacteria and parasites to farm animals has been attributed to environmental contamination of pasturelands, water supplies and feed by avian feces [ 3 , 4 , 5 ]. Migratory birds, that fly through traditional and new migratory routes, can carry ticks, posing hazards for human and animal health [ 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Di Francesco et al (2015) reported a 9.09% seroprevalence in Marsican brown bears in 2015 [ 62 ]. No detectable Brucella DNA was reported in wild birds’ fecal samples in 2021 [ 63 ]. No anti- Brucella antibodies were found in 236 chamois and 207 roe deer sampled in Italy between 1998–2001 [ 64 ].…”
Section: Resultsmentioning
confidence: 99%